Legal Aspects of Financial Technology in the Perspective of Improving Public Welfare - Pane, Musa Darwin (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
This writing aims to find out the legal aspects, especially regarding criminal policies in minimizing the occurrence of criminal acts in financial technology in Indonesia in the perspective of improving people's welfare and to find out the role of law enforcement in preventing financial technology criminal acts in Indonesia in the perspective of improving people's welfare. This paper uses normative legal research methods because the focus of the study departs from norms, regulations, legal theories and therefore has the task of systematizing positive law, using the approach: statute approach, conceptual approach, and analytical approach. The technique of tracing legal materials uses document study techniques and analysis of studies using qualitative analysis. Based on the results of the study that the need for reconstruction and/or reformulation of regulations which are the basis of the implementation of financial technology in Indonesia because they are considered not to regulate completely and in these conditions, the role of law enforcement in preventing and overcoming criminal acts has a strategic position because it is part of a task in carrying out the protection and protection of the community in realizing public welfare. Based on this the authors argue that in addition to internal reform in reconstruction and/or reformulation, external improvement is also needed through ratification from various countries and governments should be related to the implementation of financial technology in one door under the government so that supervision will be better and the government to innovate financial technology as an alternative in realizing public welfare.